Avaliação de uma experiência diferenciada de educação de jovens e adultos - Guedes, Edinalda (2008)
The objective of this research is to evaluate the differentiated experience of a school for young and adult individuals in the city of Campinas. The motivation for this work arose from the evident necessity to reflect upon and evaluate the modular structure applied to YAE, which has been used for ten years now, more precisely, since 1996, at first it was presented as a local government approved, experimental project only, as an alternative with the intent to lower the school year failing and drop out rates, which have been commonplace amongst young and adult students throughout the Brazilian education history. The school was born in the 90´s, in a time of a broad-spectrum discussion, national and international, focusing on the public policies and state responsibility concerning the assurance of citizens´ right to education, in any age. The research was aimed at collecting answers to questions I had made, as the principal of the school such as: Is the experience of learning the contents of a module able to make significant difference regarding the quality factor in the lives of YAE students? Is the quality defferential only because of the module organization or would there be other factors within the school´s daily routine that would help improve the students´ feelings of accomplishment? Which would be the pros and cons within the school that could have influence on the educational practice? Looking into the experience of authors involved with the hardships related to the education and evaluation of young and adult students, such as Freire, Arroyo, Haddad, Oliveira, Ribeiro, Paiva, Cappelletti, Abramowicz, Sobrinho, Afonso, Galindo, Belloni, De Sordi, Alaiz and others, I seek theoretical support for this research. The methodological option was for case study, given the uniqueness of the subject of the investigation: a school specific for young and adult students. Qualitative and quantitative aspects were focused upon, being the first prioritized, but within a sense of integration and complementation. The collection of empirical data was realized through a critical analysis of the school´s main official document: its Pedagogical Political Project, and through the application of a questionnaire to various individuals involved with the school. The categories of analysis contemplated in the evaluation of the school were: its structure and its mode of functioning, the periods of school time and recess in the learning process, its curriculum and overall management. The research leads to the acknowledgement that this particular school provides a differentiated reality and that the way in which it is organized has presented a satisfactory response in the education of young and adult students